2018
DOI: 10.1016/j.toxrep.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metal levels in foodstuffs from the Region of Valencia (Spain)

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
7
22
0
Order By: Relevance
“…The maximum Cd concentration obtained in tomatoes (0.660 mg/kg, dry weight) in the current study was three times higher than that reported by Mohod [ 36 ] from Amravati, India, but lower than that reported by Labhade [ 37 ] from Nashik, Murad Basha et al [ 46 ] from Andhra Pradesh, India, and quite lower than that reported by Murad Basha et al [ 44 ] from Jamaica. Further, the concentrations reported by Hadayat et al [ 38 ] from Florida (USA) in both organic and nonorganic tomatoes were considerably lower than those from the present study, the same happened with the concentrations reported by Marín et al [ 45 ] from Valencia. For Cd content in lettuce, the dry weight results obtained by the present study were largely lower than those reported in Croatia [ 1 ], Argelia [ 5 ], and India [ 37 ], but higher than the value assessed in Valencia [ 45 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The maximum Cd concentration obtained in tomatoes (0.660 mg/kg, dry weight) in the current study was three times higher than that reported by Mohod [ 36 ] from Amravati, India, but lower than that reported by Labhade [ 37 ] from Nashik, Murad Basha et al [ 46 ] from Andhra Pradesh, India, and quite lower than that reported by Murad Basha et al [ 44 ] from Jamaica. Further, the concentrations reported by Hadayat et al [ 38 ] from Florida (USA) in both organic and nonorganic tomatoes were considerably lower than those from the present study, the same happened with the concentrations reported by Marín et al [ 45 ] from Valencia. For Cd content in lettuce, the dry weight results obtained by the present study were largely lower than those reported in Croatia [ 1 ], Argelia [ 5 ], and India [ 37 ], but higher than the value assessed in Valencia [ 45 ].…”
Section: Resultssupporting
confidence: 87%
“…Further, the concentrations reported by Hadayat et al [ 38 ] from Florida (USA) in both organic and nonorganic tomatoes were considerably lower than those from the present study, the same happened with the concentrations reported by Marín et al [ 45 ] from Valencia. For Cd content in lettuce, the dry weight results obtained by the present study were largely lower than those reported in Croatia [ 1 ], Argelia [ 5 ], and India [ 37 ], but higher than the value assessed in Valencia [ 45 ]. This heterogeneity could be due to several external factors that could affect the TM content in natural products, such as the initial metal content in the crop soils and the environmental pollution near the cultivation sites.…”
Section: Resultssupporting
confidence: 87%
“…The comparison among the levels revealed the highest average values in cured sausage (0.23 μg g −1 ), followed by würstel (0.22 μg g −1 ), salami, and mortadella having the same contaminant degree (0.20 μg g −1 ) and raw ham (0.19 μg g −1 ), while the lowest levels were in baked ham (0.15 μg g −1 ). Comparing with the results of other studies, the average concentrations obtained here were similar to those reported in processed meat from India [63] and Spain [52], but notably lower than those in hot dogs from Bangladesh [60] and in other meat products from Spain [61]. There are no set standards for concentrations of this element in meat by European Union, while the United States Department of Agriculture (USDA) has established a level of 1.0 μg g −1 [49], which was not exceeded in any samples in this study.…”
Section: Chromiumsupporting
confidence: 90%
“…The amount of Pb an individual ingests via food is largely dependent on the Pb concentrations found in the soil, air, and water that the food was grown in Bolger et al [ 24 ], Khandekar et al [ 25 ] and Marin et al [ 26 ]. Anthropogenic sources of Pb, such as the proximity to industries producing Pb emissions impact the levels of Pb in food.…”
Section: Discussionmentioning
confidence: 99%